Boris Johnson's Policy Analysis on Maritime Security in the North Atlantic - Triyani, Triyani; Soemantri, Asep Iwa; Prakoso, Lukman Yudho; Suwarno, Panji; Ruslinar, Meli; Faisal, Muhamad; Zahra, Raesha Syahnaz; Oktaviandra, Yosyea; Novitasari, Yussie (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study analyses Boris Johnson’s policies on maritime security in the North Atlantic, with a focus on naval modernisation and collaboration with NATO. The study finds that Johnson’s policies focus on improving maritime defence technology and strengthening multilateral cooperation in the face of the Russian submarine threat. Although Brexit has changed the UK’s relationship with the European Union, the UK has maintained its role in maintaining maritime stability through NATO. The results of this study demonstrate the effectiveness of Johnson’s policies in addressing security challenges in the North Atlantic, although there is a need for continued investment in maritime defence technology. Recommendations for further research include longitudinal studies and research on the role of technology.